Dietary protein to starch metabolizable energy ratios alter growth performance and gastrointestinal microbiota of calves - Chen, Xue; Han, Zhiyi; Dong, Jianan; Xiao, Jun; Zhao, Wei; Rong, Jiye; Aschalew, Natnael D.; Zhang, Xuefeng; Qin, Guixin; Zhen, Yuguo; Sun, Zhe; Wang, Tao (Frontiers in Microbiology, 2023)
The diet structure is very important for the growth and development of calves. This study aimed to investigate the effects of dietary protein-to-starch metabolizable energy ratios (DPSRs) on growth performance, blood index, and gastrointestinal microbiota of calves. Forty-eight Holstein bull calves were fed six dietary DPSRs including A20-35 (20% CP and 35% starch), B20-30, C20-25, D22-35, E22-30, and F22-25 at d 4 to d 60, and then changed to another six dietary DPSRs at d 61 to d 180 (A18-30, B18-27, C18-24, D20-30, E20-27, and F20-24). Twelve calves (d 60) from groups A20-35, C20-25, D22-35, and F22-25 (n = 3) and another twelve calves (d 180) from groups A18-30, C18-24, D20-30, and F20-24 (n = 3) were euthanized. The growth performance parameters were measured. Blood, ruminal fluid, and cecum digesta were collected for further analysis. Results showed heart girth gain of B18-27 was significantly higher than A18-30, C18-24, and heart girth gain (d 180) was significantly affected by protein × starch (DPSRs; p < 0.05). Blood urea nitrogen (BUN; d 60) in C20-25 was significantly higher than A20-35 and B20-30 (p < 0.05). The BUN (d 180) in D20-30 was significantly higher than A18-30 (p < 0.05). The BUN was significantly affected by protein × starch (p < 0.05) on d 60. The albumin (ALB) levels in C20-25 and C18-24 were significantly higher than that in A20-35 on d 60 and A18-30 on d 180, respectively (p < 0.05). The ALB level in D22-35 on d 60 and E20-27 on d 180 was significantly higher than that in other groups (p < 0.05). The ALB level was significantly affected by protein and starch, respectively, on d 60 (p < 0.05). In the rumen, the genera Roseburia (C20-25) and Dialister (D22-35), Prevotellaceae UCG-001 (C18-24), Erysipelotrichaceae UCG-002, and Anaerovorax (F20-24) were found in significant higher relative abundances than those in other groups (p < 0.05). In the cecum, the genera Bacteroides and Eisenbergiella (F22-25), Ruminiclostridium_1 and Candidatus Stoquefichus (A18-30), Erysipelotrichaceae UCG-004 and Tyzzerella 4 (D20-30), and Prevotellaceae UCG-003 and Klebsiella (F20-24) were found in significant higher abundances than those in other groups (p < 0.05). Collectively, these results indicated that the heart girth, BUN, ALB, and gastrointestinal microbiota responded distinctly to differing DPSRs.